2007
DOI: 10.1016/j.bbi.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related fatigue: Links with inflammation in cancer patients and survivors

Abstract: Fatigue is one of the most common and distressing side effects of cancer and its treatment and may persist long after successful treatment completion. Emerging evidence suggests that inflammatory processes may be involved in cancer-related fatigue both during and after treatment. In this review, we consider the evidence for an association between inflammation and fatigue in cancer patients and survivors. Further, we identify potential mechanisms for persistent inflammation, focusing on the HPA axis. Risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(171 citation statements)
references
References 49 publications
6
160
1
4
Order By: Relevance
“…Earlier research has suggested that increased proinflammatory cytokine activity and increased cytokine production in response to lipopolysaccharides are associated with chronic fatigue. 9,13,15,24 Our findings support this hypothesis to some extent, because many of the core genes are involved in cytokine and stress responses, and the gene sets identified are part of the immune system. Our results indicate that a B-cell-mediated inflammatory process might underlie fatigue.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Earlier research has suggested that increased proinflammatory cytokine activity and increased cytokine production in response to lipopolysaccharides are associated with chronic fatigue. 9,13,15,24 Our findings support this hypothesis to some extent, because many of the core genes are involved in cytokine and stress responses, and the gene sets identified are part of the immune system. Our results indicate that a B-cell-mediated inflammatory process might underlie fatigue.…”
Section: Discussionsupporting
confidence: 73%
“…5,7,8 Some studies have investigated the role of the immune system and, in particular, the role of cytokines in relation to fatigue in breast cancer survivors. [9][10][11][12][13][14][15] Fatigued breast cancer survivors have been shown to have significantly higher levels of proinflammatory cytokines and circulating T lymphocytes compared with non-fatigued survivors. 9,10,15 Bower et al 11,12 showed that fatigued breast cancer survivors had an altered diurnal cortisol rhythm, and, compared to non-fatigued survivors, a blunted cortisol response to experimental stressors.…”
Section: Introductionmentioning
confidence: 99%
“…6 Monk et al observed in advanced cancer patients that the use of Etanercept (Enbrel), which works by reducing the effects of TNF, safely and effectively reduced their reported levels of fatigue. 94…”
Section: Pharmacotherapymentioning
confidence: 99%
“…[19][20][21][22] Not only is fatigue highly prevalent, but it is also reported to be the most distressing symptom, affecting the patient's quality of life and daily activities negatively. [19][20][21] Given this wide prevalence among cancer patients, and even cancer survivors several years after complete remission, 23,24 it is clear that the underlying mechanisms may deeply involve various components of human physiology. Thus, possible causes of fatigue can involve the periphery (eg, neuromuscular junctions and proprioceptive fibers), the central nervous system (eg, neuromediators imbalance, inflammatory cytokines, hormonal dysfunction, autonomic dereg ulation, and circadian disruption), and comorbid conditions, such as anemia, cachexia, and depression.…”
Section: Fatigue In Cancer Patientsmentioning
confidence: 99%